In vitro Mass Propagation from Shoot Tip Explants of Vernonia cinerea (L.) Less. An Antioxidant, Anti-inflammatory Medicinal Plant (Plant Tissue Culture and Biotechnology, 2011)
Plantlets were regenerated from the shoot tip explants of Vernonia cinerea (L.) Less. in MS supplimented with BA and Kn. Maximum number of shoots in BA (13.32 mg/l) and roots in IBA (7.38 mg/l) developed. The rooted plantlets were successfully established in the field.   Key words: Vernonia cinerea, Mass propagation, Shoot tip explants, Antioxidant, Medicinal plant   D.O.I. 10.3329/ptcb.v20i2.6892   Plant Tissue Cult. & Biotech. 20(2): 127-131, 2010 (December)